1996
DOI: 10.1128/jb.178.22.6496-6507.1996
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of diaminopimelate, the precursor of lysine and a component of peptidoglycan, is an essential function of Mycobacterium smegmatis

Abstract: Diaminopimelate (DAP) is a unique metabolite used for both the biosynthesis of lysine in bacteria and the construction of the peptidoglycan of many species of bacteria, including mycobacteria. DAP is synthesized by bacteria as part of the aspartate amino acid family, which includes methionine, threonine, isoleucine, and lysine. Aspartokinase, the first enzyme in this pathway, is encoded by the ask gene in mycobacteria. Previous attempts to disrupt this gene in Mycobacterium smegmatis were unsuccessful, even wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
167
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 64 publications
2
167
1
Order By: Relevance
“…Mesodiaminopimelate (DAP) is an essential component of the peptidoglycan layer of bacterial cell walls, and disruption of its biosynthesis results in cell death, probably due to instability of the peptidoglycan (Pavelka & Jacobs, 1996). L-Lysine is produced by the enzymatic decarboxylation of meso-diaminopimelate and is essential for protein synthesis.…”
mentioning
confidence: 99%
“…Mesodiaminopimelate (DAP) is an essential component of the peptidoglycan layer of bacterial cell walls, and disruption of its biosynthesis results in cell death, probably due to instability of the peptidoglycan (Pavelka & Jacobs, 1996). L-Lysine is produced by the enzymatic decarboxylation of meso-diaminopimelate and is essential for protein synthesis.…”
mentioning
confidence: 99%
“…The key to this is a suitable counterselectable marker, such as sacB (conferring sucrose sensitivity), rpsL (conferring streptomycin susceptibility in a streptomycin-resistant background) or galK (conferring 2-deoxygalactose susceptibility) [14,[27][28][29]. Others have shown that sacB does not work in M. abscessus, and the rpsL system requires a pre-existing streptomycin resistance mutation in the choromosomal copy of rpsL, which complicates strain construction [16,23,29]. Additionally, in preliminary experiments (not shown), we found it difficult to isolate streptomycin-resistant mutants that could be used with our previously developed rpsL suicide vectors.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids used for recombination were prepared using Qiagen columns (Qiagen, Valencia, CA) and, when required, the DNA was UV treated by irradiating 15 µl of a~0.5 mg ml À1 DNA preparation on a sterile, lidless polystyrene Petri dish in a UV Stratalinker 2400 (Agilent Technologies, Santa Clara, CA) on the default setting for timed exposure. One microlitre of each irradiated suicide vector was used for each electroporation, under conditions previously described for M. smegmatis [23]. Southern blotting was done with genomic DNA using the Amersham ECL DIRECT Nucleic acid [24], using iProof High-Fidelity DNA Polymerase from Bio Rad (Hercules, CA).…”
Section: Dna Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that Mycobacterium cell walls are characterized by an unusual high DAP content. Moreover gene-knock out experiments with Mycobacterium smegmatis has demonstrated the essentiality of DAP pathway for the bacteria, where the absence of DAP results in cell lysis and death [12].…”
Section: Introductionmentioning
confidence: 99%